Care and wellbeing across Europe - a research frame for studying migrant families - Brandt, Martina; Kaschowitz, Judith (Technische Universität Dortmund, 2024)
All over Europe, the question of sustainable care for the older people gains attention. Although the number of older migrants is increasing significantly, to date only little empirical research deals with migrant family care. In this paper, we thus give an overview of theoretical models on care and wellbeing and adjust them to (different groups of) migrants across Europe. We then present (rare) empirical studies on (in-) formal care and wellbeing, asking: do migrants give/use care more likely than natives and if so, why? Are migrant caregivers more or less burdened compared to non-migrant caregivers? How did the pandemic affect migrant caregivers? Based on our assessments of the state of quantitative research we highlight limitations and propose paths for future research on care in migrant families.
Ethnic and racial studies; 47(14)
Keywords: Ageing; Caregiving; COVID-19; Health; Migration; Social inequality; 370; 150; 300